Peningkatan Kualitas Air Danau Sukaramai Kecamatan Tapung Hulu Kabupaten Kampar dengan Metode Filtrasi - Lusi Dwi Putri (Jurnal Teknik Sipil Unaya, 2022)
Sukaramai village is very difficult to get clean water. The surrounding community uses the lake water for their daily needs but not for consumption. Physically, the water quality of Lake Sukaramai is cloudy and contains TDS. One alternative that can be applied so that lake water can be consumed is the filtration method. The purpose of this study was to determine the decrease in turbidity, total dissolved solids (TDS) and increase in pH in Lake Sukaramai water produced using an activated carbon-silica sand filter with a diameter of 0,1-0,5 with a media thickness of 30 cm and residence time. for 6 hours. The test will be carried out at the Fluid Mechanics and Hydraulics Laboratory of Lancang University. Based on the results of laboratory tests, it shows that the size of the decrease produced by activated carbon-silica sand filter media is 0,1-0,5 mm in diameter with turbidity parameters 93,94%, TDS 89,26% and pH 5,52%. This shows that activated carbon-silica sand filter media with a diameter of 0,1-0,5 mm is effective in reducing turbidity, TDS (total dissolved solids), and pH in Sukaramai Lake water